Selected Factors of Vascular Changes: The Potential Pathological Processes Underlying Primary Headaches in Children - Joanna Sordyl; Ilona Kopyta; Beata Sarecka-Hujar; Pawel Matusik; Tomasz Francuz; Ewa Malecka-Tendera (MDPI AG, 2022)
Background: The prevalence, social consequences and complicated pathogenesis make headaches in children a significant clinical issue. Studies in adults suggest that primary headaches could be the first sign of atherosclerosis and platelet aggregation. Aim: To analyze the blood levels of selected biomarkers of vascular changes potentially associated with a higher risk of atherosclerosis in children with primary headaches. Methods: The medical family history, brain-derived neurotrophic factor (BDNF), soluble CD40 ligands (sCD40L), endothelial plasminogen activator inhibitor (PAI I), vascular endothelial growth factor (VEGF) and intima-media thickness (IMT) measurements were performed in the 83 children (52 with primary headaches, 31 controls). Selected factors were compared with basic laboratory parameters that are potentially related to atherosclerosis: C-reactive protein (CRP) and lipid concentration. Results: There were no significant differences in biomarkers of vascular changes in the study group and controls in general. In the study group, boys had a higher BDNF level than girls (p = 0.046). Normal-weight migraine patients had significantly higher PAI-I levels than controls (p = 0.034). A positive correlation between PAI-1 and triglycerides (TG) was observed. IMT did not differ between children with primary headaches and controls; however, IMT showed a positive correlation with BMI z-score and TG. Children with headaches had, more often, a positive family history of cardiovascular disease (p = 0.049). Conclusions: There were no clear clinical changes indicative of atherosclerosis in the study population. However, some trends are visible. Primary headaches are more often related to a family history of cardiovascular diseases. IMT is associated with TG levels and BMI z-score. The measured biomarkers of vascular changes show mutual relations.